2013
DOI: 10.1007/s10806-013-9440-4
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of E-Numbers: Ethical, Aesthetic, and Cultural Concerns in the Dutch Discourse on Food Additives

Abstract: Persistent public distrust of food additives is often explained in terms of safety and health issues. The broad variety of ethical, aesthetic, and cultural concerns tends to be structurally ignored by food engineers and occasionally even by consumers themselves. The public controversy of food additives-commonly known as ''E-numbers''-in the Netherlands is a case in point. Two discursive mechanisms prevent these concerns from becoming legitimate public issues: irrationalization and privatization. But these cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
1
21
0
2
Order By: Relevance
“…The use of food additives in food manufacturing has been a public health issue for many years (Haen 2014, Saltmarsh 2013. A report issued by the European Food Safety Authority (EFSA) in 2010 showed that 25% of people surveyed were "very worried" about food additives and a further 41% were "fairly worried" (EFSA 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The use of food additives in food manufacturing has been a public health issue for many years (Haen 2014, Saltmarsh 2013. A report issued by the European Food Safety Authority (EFSA) in 2010 showed that 25% of people surveyed were "very worried" about food additives and a further 41% were "fairly worried" (EFSA 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The current sensory study also showed that curing had no effect on liking of fermented sausage. Arguably nitrite could be omitted from fermented sheepmeat sausage, perhaps a commercial advantage in sophisticated markets where there is a widespread, but misplaced, distrust of additives to foods (Haen ). Any real or perceived problems arising from nitrite‐derived nitrosamine formation can easily be prevented by ascorbic acid addition (Martin ).…”
Section: Discussionmentioning
confidence: 99%
“…Current research also suggests that consumers are worried and would like to be better informed about the potential health risks of food additive use and consumption [16]. However, many nutritionists still hold on to the claim that food additives are an essential element in the spread of snaking culture as well as the commercial success of so-called junk foods, which are often held responsible, at least in part, in the increased prevalence of non-communicable diseases [12].…”
Section: Toxicological Risk For Biscuits Consumptionmentioning
confidence: 99%